A prospective study of clinical pattern of febrile thrombocytopenia in government general hospital, Nalgonda - Reddy, Yadavendra C.; ., Karunakar (International Journal of Advances in Medicine, 2021)
Background: Febrile thrombocytopenia is a usual condition caused by infections such as dengue, malaria, typhoid, septicimea and certain viral infections. The present study is aimed to study the aetiology of fever with thrombocytopenia and the clinical presentation in the patients admitted in Government General Hospital. Methods: This prospective observational study was done from August 2019 to September 2019 in Government General Hospital Nalgonda. A total of 100 cases male and female admitted with febrile thrombocytopenia were studied based on inclusion and exclusion criteria. All patients were done routine investigations and ELISA test for dengue done in susceptible patients. Patients below 12 years, pregnant women and patients with previous bleeding manifestations were excluded from the study. The study was carried out in all patients fulfilling the inclusion and exclusion criteria. Results: A total of 100 patients 60 females and 40 males presented during the study period. Most of the fevers with low platelet count were viral 30 (30%), dengue 25 (25%), typhoid 20(20%), malaria 15 (15%), hepatitis 10 (10%). The patients presented with fever 25 (25%), nausea 20 (20%), headache 20 (20%) abdominal ain 15 (15%), diarrhea 10 (10%), bleeding manifestations 5 (5%), myalgia 5 (5%). Conclusions: It was observed from the study that the viral infections were predominant cause for the fevers with thrombocytopenia followed by dengue, typhoid and malaria, furthur it was observed that apart from fever nausea and headache were predominant symptoms in patients presenting with febrile thrombocytopenia. Major complications were avoided by timely admission and proper care of the patients.